Risk Factors for Cardiovascular Disease in Young Adults - López- Panata, Jonathan Alexander (2022)
Cardiovascular diseases are the leading cause of death (1.9 million annually), which can be prevented with lifestyle modifications. The World Health Organization has defined that in the Americas, they usually affect both sexes equally, with 30% of premature deaths in the poorest quintile. Therefore, the regional strategy aims to reduce mortality figures by 25%. The present study identified cardiovascular risk factors in a population of young adults from the parish of Izamba. A descriptive study was carried out for which the Questionnaire of Risk Factors of the Ministry of Health of Mexico and the International Questionnaire of Physical Activity IPAQ was used, the sample was made up of 30 young members of the EANJ of the name of Jesus of the parish Izamba, Tungurahua Province, Ecuador. The study described the presence of several direct and indirect non-modifiable and modifiable risk factors, as well as other related ones, where the following stand out: Non-modifiable factors (Male Sex, History in first-degree relatives of early cardiovascular disease (arterial hypertension, familial hypercholesterolemia and type 2 diabetes mellitus); among the direct modifiable risk factors (being diagnosed and / or treated for arterial hypertension, type 2 diabetes mellitus and hypercholesterolemia); Indirect modifiable risk factors (obesity and sedentary lifestyle) and other related factors (hormonal, toxic habits, consumption of coffee, cocaine, smoking, psychological factors and metabolic disorders), which makes a nursing intervention strategy necessary for its control.